Syncretism of Slametan Tradition As a Pillar of Islam Nusantara - Muqoddam, Faqihul; Maghfiroh, Virgin Suciyanti (Institut Agama Islam Negeri Madura, 2019)
Slametan is a tradition which is still embraced by Javanese in general, especially who is in rural areas. The slametan has different characteristics in each region that due to heterogeneity factors. The research purposes to describe slametan forms, process, and syncretism patterns of slametan tradition in Ngaringan village, Gandusari district, Blitar. The research used a qualitative tradition with descriptive narrative approach which is thematic analysis for data analysis process used. The research were participated by public figures in Ngaringan village. Data collection with in-depth interviews and observation. It found (1) Slametan forms generally includes birth, death, marriage, cleaning the village, feast day, welcoming Ramadhan, celebrating after coming back from abroad for the work, and celebrating when harvest comes. (2) The slametan process consists of serving food (such as; chicken in ingkung form, buceng rice, jenang colors red and white, jenang sengkolo) and prayer. (3) The slametan tradition is a pattern of syncretism between Java and Islam as a pillar of â€œIslam Nusantaraâ€. The Slametan had already existed as a Javanese ritual before Islam came than they were merged into the one. The research conclusion reveals that the slametan tradition is a ritual which is combining between Javanese and Islamic traditions than became characteristic of â€œIslam Nusantaraâ€.